Histopathology and Ultrastructure Features of the Midgut of Adult Females of the Tick Amblyomma cajennense Fabricius, 1787 (Acari: Ixodidae) in Various Feeding Stages and Submitted to Three Infestations - Caperucci, Debora; Camargo Mathias, Maria Izabel [UNESP]; Bechara, Gervasio Henrique [UNESP] (Taylor & Francis Inc, 2009)
The digestive tube of the tick Amblyomma cajennense is responsible for the digestion during feeding on the host. This study analyzed the midgut of unfed, partially engorged, and fully engorged fed females as well as three infestations in rabbits. In A. cajennense, the digestive tube is long and from the midgut, two pairs of diverticula ramify and lead to a blind end. In some midgut regions were observed for the first time in ticks, structures termed here "nodules." The midgut of unfed females possesses a pseudostratified epithelium composed of digestive and generative cells. In partially engorged and engorged females at 1st infestation and partially engorged at 2nd infestation, the epithelium becomes stratified. In partially engorged females at 2nd infestation, the epithelium exhibits a third cell type: secretory cell. So the intestinal epithelium undergoes several changes during the feeding process in ticks at subsequent infestations. As infestations progress in the same host, the latter becomes more resistant and female ticks require more days to complete their feeding cycle, which in A. cajennense is 25 days.
Keywords: Amblyomma cajennense; Midgut; morpho-histology; Reinfestation; SEM; Ticks